Scanning electron microscopic study of antennal of the female Bee louse fly Braula coeca Nitzsch (Diptera: Braulidae) - Ali Agleyo, Al-Hashmi (Al-Mukhtar Journal of Sciences, 2026)
The antenna of the female bee louse Braula coeca consists of a scape, a pedicel and a Funicle (enlarged basal flagella subsegment). The scape is not visible and does not carry any type of sensilla. The pedicel is approximately triangular in cross section and it carries a group of long grooved articulated bristles. The Funicle is cover with microtrichia; it contains three types of sensilla: long sharp-tipped sensilla, basiconica sensilla and ribbed peg sensilla. There is only one olfactory pit on the basal side of the Funicle and it contains 3 – 4 ribbed peg sensilla. The arista long, cylindrical, fringed and on the first quarter of the basal part, there are very small six cone-shaped sensilla on the dorsal surface. The suggested function of each sensilla was based on comparison with results of other investigation on similar sensilla.